2015
DOI: 10.1177/1084822315569279
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and Views of the Discharge Planning Process Among Swedish District Nurses and Home Care Organizers

Abstract: Discharge planning is an important care process, but deficits in planning are common. The aim of this study was to explore district nurses' (DNs) and home care organizers' (HCOs) experiences and views of the workflow during the discharge planning process (DPP). Demands, workload, time, collaboration, and engagement, together with knowledge and professional confidence, are factors that influence workflow and outcome of the DPP for DNs and HCOs. Strengths and obstacles at the organization, group, and individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
4
0
2
Order By: Relevance
“…Deficits in communication and transfer of information about medication between healthcare providers have been identified as the leading cause of medication errors in transitional care (Allen, Ottmann, & Roberts, ; Hesselink et al., ; Johnson, Guirguis, & Grace, ; Nosbusch, Weiss, & Bobay, ). The rising number of elderly and chronically ill people, the trend towards shorter hospital stays and the growing effort to deliver health care in the municipalities have changed the cross‐sectoral roles and work of nurses (Nordmark, Zingmark, & Lindberg, ) and led to an increasing demand for more effective communication and coordination between hospital and primary care providers (Hesselink et al., ). Research indicates that interventions that aim at improving documentation and transferring of information can reduce medication errors (Midlöv, Bergkvist, Bondesson, Eriksson, & Höglund, ), improve care coordination (Laugaland, Aase, & Barach, ) and reduce rates of readmissions and length of stay (Allen et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deficits in communication and transfer of information about medication between healthcare providers have been identified as the leading cause of medication errors in transitional care (Allen, Ottmann, & Roberts, ; Hesselink et al., ; Johnson, Guirguis, & Grace, ; Nosbusch, Weiss, & Bobay, ). The rising number of elderly and chronically ill people, the trend towards shorter hospital stays and the growing effort to deliver health care in the municipalities have changed the cross‐sectoral roles and work of nurses (Nordmark, Zingmark, & Lindberg, ) and led to an increasing demand for more effective communication and coordination between hospital and primary care providers (Hesselink et al., ). Research indicates that interventions that aim at improving documentation and transferring of information can reduce medication errors (Midlöv, Bergkvist, Bondesson, Eriksson, & Höglund, ), improve care coordination (Laugaland, Aase, & Barach, ) and reduce rates of readmissions and length of stay (Allen et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that cross‐sectoral communication between nurses is characterised by inadequate, inaccurate and untimely information exchange (Brown et al., ; Nordmark et al., ; Olsen, Hellzén, & Enmarker, ; Payne, Kerr, Hawker, Hardey, & Powell, ), especially in relation to medication (Ellenbecker, Frazier, & Verney, ; Vogelsmeier, ). The introduction of e‐message systems is intended to play a key part in strengthening information exchange and communication between nurses in different settings (Allen et al., ; Hesselink et al., ), and technology systems are considered to be effective in ensuring safe medication administration (Van de Castle et al., ; Vogelsmeier, ).…”
Section: Introductionmentioning
confidence: 99%
“…The conceptualization, definition and content of home health care varies throughout the world, and numerous terms are used to describe the concept of care given in the home, including homecare services, home help services, home care, home based care, community health care and district nursing (Bing-Jonsson et al, 2013, Bôas and Shimizu, 2015, Drennan, 2019, Nielsen and Jørgensen, 2016. The nursing skill mix required in home health care and the titles given those providing such care differ throughout the world: in Norway, registered nurses and assistant nurses provide such care (Bing-Jonsson et al, 2013); in Belgium, home nurse and health care assistants (De Vliegher et al, 2014, De Vliegher et al, 2016; in Denmark, home health care givers (Nielsen and Jørgensen, 2016); in Sweden, home care assistants and district nurses (Craftman et al, 2018, Nordmark et al, 2015; in the United Kingdom (UK) and New Zealand, district nurses (Drennan, 2019, Walker andHendry, 2009); in the United States of America (USA) registered nurses, licensed practice nurses, home health aides and certified nursing assistants (Luo et al, 2013); and in Ireland, public health nurses (Brady et al, 2007).…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Lebih lanjut Henke, Karaca, Jackson, Marder, & Wong, mengatakan pelaksanaan discharge planning dengan kualitas yang baik berhasil mengurangi penolakan tindakan dari pasien yang diterima kembali (2017). Pendapat lainnya mengatakan bahwa selama pasien dirawat di rumah sakit, perawat primer dan petugas kesehatan masyarakat dilibatkan dalam discharge planning process untuk merencanakan pemulangan, mendiskusikan kemampuan pasiennya, kebutuhan perawatan medis, dan perawatan lebih lanjut (Nordmark, Zingmark, & Lindberg, 2015).…”
Section: Hasilunclassified